How do you solve #3(x − 1) − (x + 5) = 2 #?

1 Answer
Mar 18, 2016

Answer:

#x= {5}#

Explanation:

Given

#3(x-1) - (x+5) = 2#

Step 1: Using the distributive law to simplify the expression

#3x- 3 -x -5 = 2#

Step 2: Combine like terms in the left hand side to get

#2x-8 = 2#

Step 3: Add 8 to both side, to isolate variable

#2x = 2 + 8#

#2x = 10#

Step 4 : Divide both side by 2 to get

#(2x)/2 = 10/2 #

#x= 5#

Check your solution:

#3(5-1) -(5+5) ? = 2#

#3(4) -10 = 2#

#12- 10 = 2#

#2= 2#